Construction of Islamic Education Curriculum in the Philosophy of Islamic Education Perspective - Bakti Nasution, Hasan; Ahyar, Saiful; Abidin, Zainal (Edumaspul: Jurnal Pendidikan, 2022)
This research focuses on Construction Of Islamic Education Curriculum In The Philosophy Of Islamic Education Perspective, the method used in this research is library research approach. while the results of the study show that the Islamic education curriculum aims to contribute to achieving comprehensive and integrated development for individual students, opening the veil of talent, willingness and developing desired interests, skills, knowledge, skills, and attitudes; instilling good habits, morals and attitudes and basic skills to gain knowledge; prepare them to assume the responsibilities and roles they assume in society; develop religious, cultural, thought, social, and political awareness in themselves.